MEU CORPO, MEU POST, MINHA LUTA: Ciberativismo gordo e as possibilidades da comunicação contraperformativa feminista no Instagram Brasil - RUBIA SIBELE NOGUEIRA RODRIGUES (2023)
The wide dissemination of feminist thought over the internet has enabled a greater amplification and nuance of feminist cyberactivism, within which the power of the fat cyberactivist movement develops on the social network Instagram. Considering this context, the present work aimed to investigate, based on the methodology of Categorical Content Analysis (CA), the cyberactivist movements, Movimento Corpo Livre (@movimentocorpolivre) and Vai Ter Gorda (@vaitergorda), to analyze how the communicative expressions used are developed to make visible and mobilize the themes of fat acceptance movement. The period to be studied includes 45 days (September 15th, 2022 to October 31th, 2022). The categorical CA methodology was chosen because it is a quantitative but also a qualitative technique that seeks to allow the creation of inferences about certain content. Resulting in three chapters, with chapter one presenting the investigation of the body as a political field, in view of its role both in the processes of female submission and in the struggles for emancipation. In chapter two, there is the contextualization of social networks and the Instagram platform as the stage of network activism, having as main theoretical references the Brazilian researcher of social networks and information flows in cyberspace, finally, the last chapter presents the exploratory of the object of study in dialogue with the previously exposed concepts: Movimento Corpo Livre and Vai Ter Gorda, through a structured categorical AC that made it possible to better understand the potential of each of the studied profiles, as well as their main communication strategies and even conquests, such as cyberactivist movements. In view of all this, it is concluded that the profile Vai Ter Gorda, as well as Movimento Corpo Livre, with their cyberactivist actions on Instagram, are characterized as representatives of the brazilian fat cyberactivist movement, acting on several fronts, in raising awareness, denouncing, fighting fatphobia, education and celebration of body diversity. In this feminine and feminist emancipatory movement, we understand that our bodies are a fundamental part of our experience as subjects, and therefore, these subjugation and liberation movements need to be part of women's struggle.